Control of cambium initiation and activity in Arabidopsis by the transcriptional regulator AHL15 - Rahimi, Arezoo; Karami, Omid; Lestari, Angga Dwituti; Werk, Tobias de; Amakorová, Petra; Shi, Dongbo; Novák, Ondřej; Greb, Thomas; Offringa, Remko (Current biology, 2022)
Plant secondary growth, which is the basis of wood formation, includes the production of secondary xylem, which is derived from meristematic cambium cells embedded in vascular tissue. Here, we identified an important role for the Arabidopsis thaliana (Arabidopsis) AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED 15 (AHL15) transcriptional regulator in controlling vascular cambium activity. The limited secondary xylem development in inflorescence stems of herbaceous Arabidopsis plants was significantly reduced in ahl15 loss-of-function mutants, whereas constitutive or vascular meristem-specific AHL15 overexpression produced woody inflorescence stems. AHL15 was required for enhanced secondary xylem formation in the woody suppressor of overexpression of constans 1 (soc1) fruitfull (ful) double loss-of-function mutant. Moreover, we found that AHL15 induces vascular cambium activity downstream of the repressing SOC1 and FUL transcription factors, most likely similar to how it enhances lateral branching by promoting biosynthesis of the hormone cytokinin. Our results uncover a novel pathway driving cambium development, in which AHL15 expression levels act in parallel to and are dependent on the well-established TDIF-PXY-WOX pathway to differentiate between herbaceous and woody stem growth.